Peningkatan Hasil Belajar Speaking Menggunakan Teknik Know, What To Know, Learned And Monologue Text - Noerdjanah Noerdjanah; Sugiono Sugiono (Poltekkes Kemenkes Surakarta, 2020)
Background: Speaking in english learning was crucial and important. An increase in english language learning is not easy. The limitation of student speaking inhibits self-development in science, technology and the arts. This study aims to determine the increase in the outcome of speaking learning using the technique of know, what to know, learned and monologue text in physiotherapy students college. Methods: A quantitavive experiment research with out control grup design. Amount of sample is 48 physiotherapy students in first grade. Instrumen to describe result of study consist of 40 questions. Students study using know, what to know, learned and monologue text during 2 month. Date was analized using paired t test. Results: Result of paired t test show that P vslue is 0,000. Based on the results the technical influence testing technique of know, what to know, learned and monologue text, there is an increase in the outcome of learning outcomes, from results pretest, postest. This can be noted there are influences of the technique of know, what to know, learned and monologue text in improving the outcome of learning physiotherapy students college of Poltekes Surakarta. Conclusion: Recommendation and implication of the study, students are expected to be able to provide new knowledge about KWL techniques that are applied in understanding monologue texts and speaking practices so that students are easy to understand a text in English and spoken in speaking prantice.